REASONS FOR THE EMERGENCE OF ENLIGHTENMENT LITERATURE IN GERMANY - D.Haydarova (American Journals, 2023)
In this article highlights of reasons for the emergence of enlightenment literature in Germany.
Keywords: emergence of enlightenment, literature, Germany, cultural development, society.